The Potential of Microbial Fuel Cells as a Dual Solution for Sustainable Wastewater Treatment and Energy Generation: A Case Study - Shajjadur Rahman Shajid; Monjur Mourshed; Md. Golam Kibria; Bahman Shabani (Energies, 2025)
Microbial fuel cells (MFCs) are bio-electrochemical systems that harness microorganisms to convert organic pollutants in wastewater directly into electricity, offering a dual solution for sustainable wastewater treatment and renewable energy generation. This paper presents a holistic techno-economic and environmental feasibility assessment of large-scale MFC deployment in Dhaka’s industrial zone, Bangladesh, as a relevant case study. Here, treating 100,000 cubic meters of wastewater daily would require a capital investment of approximately USD 500 million, with a total project cost ranging between USD 307.38 million and 1.711 billion, depending on system configurations. This setup has an estimated theoretical energy recovery of 478.4 MWh/day and a realistic output of 382 MWh/day, translating to a per-unit energy cost of USD 0.2–1/kWh. MFCs show great potential for treating wastewater and addressing energy challenges. However, this paper explores remaining challenges, including high capital costs, electrode and membrane inefficiencies, and scalability issues.